ANALISIS PERAN GURU DALAM PEMBELAJARAN SENI BUDAYA DI SDN PROPPO 1 PAMEKASAN - Ilmi, Arifatul; M. Fadlillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research examines the role of teachers in cultural arts learning based on local wisdom at SDN Proppo 1 Pamekasan, specifically focusing on third-grade students. The problem identified is that the integration of local wisdom, particularly Kerapan Sapi as Madurese cultural heritage, has not been optimally implemented in arts and culture learning. The research aims to analyze how teachers fulfill their roles as planners, implementers, and evaluators in cultural arts learning. This study employs a qualitative method with a descriptive approach, where data were collected through interviews, observations, and documentation. The findings reveal that the implementation of teacher's role has been relatively adequate (69% of indicators met), however several critical weaknesses were identified. In planning, local wisdom is only superficially incorporated as visual illustrations without deep exploration. In implementation, learning is dominated by lecture methods and static visual media, resulting in minimal active student engagement and failure to align with the constructivist approach expected in culture-based learning. In evaluation, assessment focuses predominantly on cognitive aspects while neglecting authentic assessment of psychomotor and affective domains due to limited practical activities. Consequently, learning objectives related to aesthetic sensitivity, creativity, artistic skills, and deep appreciation of Madurese cultural heritage have not been optimally achieved. This research concludes that integrated improvements are necessary from teachers, schools, and the Education Office, particularly in mastering constructivist approaches, utilizing interactive media, designing practical activities, and implementing culture-based authentic assessment systems to create more meaningful learning rooted in students' local identity. ABSTRAK Penelitian ini mengkaji peran guru dalam pembelajaran Seni Budaya berbasis kearifan lokal di SDN Proppo 1 Pamekasan, khususnya pada siswa kelas 3. Masalah yang diidentifikasi adalah integrasi kearifan lokal, terutama Kerapan Sapi sebagai warisan budaya Madura belum optimal dalam pembelajaran seni budaya. Tujuan penelitian adalah menganalisis bagaimana guru berperan sebagai perencana, pelaksana, dan evaluator dalam pembelajaran seni budaya. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif, dimana data dikumpulkan melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa implementasi peran guru telah berjalan cukup baik (69% indikator terpenuhi), namun ditemukan beberapa kelemahan krusial. Pada aspek perencanaan, kearifan lokal hanya dijadikan ilustrasi visual tanpa eksplorasi mendalam. Dalam pelaksanaan, pembelajaran didominasi metode ceramah dan media visual statis, mengakibatkan minimnya keterlibatan aktif siswa dan tidak sesuai dengan pendekatan konstruktivis berbasis budaya yang diharapkan. Pada aspek evaluasi, penilaian terlalu fokus pada aspek kognitif dan mengabaikan penilaian autentik terhadap ranah psikomotor dan afektif karena minimnya aktivitas praktik. Akibatnya, tujuan pembelajaran untuk menumbuhkan kepekaan estetis, kreativitas, keterampilan berkarya, dan apresiasi mendalam terhadap warisan budaya Madura belum tercapai maksimal. Penelitian ini menyimpulkan bahwa diperlukan upaya peningkatan terpadu dari guru, sekolah, dan Dinas Pendidikan, terutama dalam penguasaan pendekatan konstruktivis, penggunaan media interaktif, desain aktivitas praktik, dan penerapan sistem penilaian autentik berbasis budaya, agar pembelajaran menjadi lebih bermakna dan mampu mengakar pada identitas lokal siswa.